Pemanfaatan Teknologi Digital untuk Percaya Diri dan Mental Yang Lebih Sehat - Sofi Cahyani Adiputri; Iftah Normalia Dhiaz Ufaira; Iftah Normalia (CV. ITTC INDONESIA, 2025)
This community service activity aims to increase self-confidence and mental health awareness among students of SMA Negeri 6 Tangerang Selatan through the positive use of digital technology. In the digital era, adolescents are highly exposed to social media and online platforms that may influence their psychological well-being. This program was conducted to guide students in utilizing digital technology wisely as a medium for self-development and mental health support. The methods used included interactive presentations, discussions, and digital-based learning activities. The results showed an improvement in students’ understanding of digital literacy, reduced negative digital habits, and increased self-confidence in academic and social environments. This activity demonstrates that proper guidance in digital technology utilization can contribute positively to adolescents’ mental health and personal development.